2014
DOI: 10.1002/dmrr.2625
|View full text |Cite
|
Sign up to set email alerts
|

Platelet mean volume, distribution width, and count in type 2 diabetes, impaired fasting glucose, and metabolic syndrome: a meta‐analysis

Abstract: Available data suggest that T2DM subjects tend to have higher mean platelet volume and platelet distribution width values, but nondifferent platelet count as compared with subjects without T2DM. Whether and how these morphometric changes contribute to CVD of T2DM or can be used as CVD biomarker awaits further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 76 publications
(88 reference statements)
6
61
0
2
Order By: Relevance
“…The relation between MPV and DMT2 was first reported by Sharpe and Trinick who founded a significant increase of MPV in diabetic compared with non diabetic patients [41]. This research was followed by numerous studies and with largest study conducted on 13,021 diabetic patients [14,31,[42][43][44]. Similarly, Our study results had shown significantly higher MPV in the group B compared to the group A.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The relation between MPV and DMT2 was first reported by Sharpe and Trinick who founded a significant increase of MPV in diabetic compared with non diabetic patients [41]. This research was followed by numerous studies and with largest study conducted on 13,021 diabetic patients [14,31,[42][43][44]. Similarly, Our study results had shown significantly higher MPV in the group B compared to the group A.…”
Section: Discussionsupporting
confidence: 74%
“…Platelets are a central element of the athero-thrombotic process due to their prothrombotic and proinflamatory function [8,9,10]. The association of increased MPV, PDW and decreased platelet count with disease related to endothelial dysfunction such as metabolic syndrome diabetes, coronary artery disease (CAD) and malignancy which has been shown in many studies [11][12][13][14][15]. Diabetes particularly DMT2 patients are exposed to the increased platelet reactivity due to multi factorial causes such as metabolic (e.g hyperglycemia, hypertriglyceridemia) and systemic abnormalities (eg.…”
Section: Introductionmentioning
confidence: 99%
“…[5] The association of increased MPV, PDW, P-LCR, and platelet count with diseases related to endothelial dysfunction such as metabolic syndrome, diabetes, coronary artery disease (CAD), and malignancy has been shown in many studies. [6,7,8,9] The newer hematological analyzers are giving variety of platelet parameters which helps in easy detection of change in platelet structure, which may help in early detection of prothrombotic state of the platelets. These can act as an alarm for diagnosing initiation/progression of diabetic complications.…”
Section: Introductionmentioning
confidence: 99%
“…[74] This reduced insulin sensitivity increases platelet responsiveness to platelet activators, such as thrombin. [74] Platelets from patients with diabetes tend to have a larger mean platelet volume, [75][76][77] which allows the platelets to be more metabolically and enzymatically active [74]; thus, metabolism of arachidonic acid and subsequent production of TXA 2 are increased in platelets from patients with diabetes. [72][73][74]78] Larger platelets also contain more prothrombotic mediators and have a greater surface area over which to display adhesion molecules.…”
Section: Aspirin: Antiplatelet Effects and Pharmacokineticsmentioning
confidence: 99%
“…reduced production of TXA 2 ≥ 95%). [10,88] For example, the increased platelet turnover in patients with diabetes [75,76,85] combined with the short half-life of aspirin means that newly synthesized, hyper-reactive immature platelets remain uninhibited during a considerable portion of the 24-h window of time between once-daily aspirin doses. [11] Indeed, markers of immature platelets (i.e.…”
Section: Aspirin: Antiplatelet Effects and Pharmacokineticsmentioning
confidence: 99%